CONSIDERAZIONI SUL LIBRO DI KEVIN RUDD: THE AVOIDABLE WAR (Il Politico, 2023)
Kevin Rudd’s book on “The Avoidable War”, in addition to offering an excellent review of relations and tensions between the US and China, allows us to develop some reflections on the future of the new international order, upset by dramatic conflicts, such as the war in Ukraine and the Middle East. Rudd proposes a “managed strategic competition” between US and China in order to allow a peaceful settlement of disputes, primarily that concerning the future of Taiwan. The recent meeting of the BRICS (23 August 2023) allows to broaden this perspective to the relations between North and South, thanks to the proposal of the BRICS countries for an “Inclusive Multilateralism”. If, in addition to political conflicts between states, we also consider the problems created by the environmental crisis - which threatens the survival of many animal species, including homo sapiens - the proposal for an inclusive multipolarity reinforces the line of thought developed by Rudd. A form of peaceful coexistence between large and small powers to save life on the planet is not a utopia or the dream of a naïve optimist.